2014
DOI: 10.1186/s12939-014-0081-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with healthcare avoidance among transgender women in Argentina

Abstract: IntroductionTransgender (TG) women in many settings continue to contend with barriers to healthcare, including experiences of stigma and discrimination. Argentina has a universal health care system and laws designed to promote healthcare access among TG women. However, little is known about barriers to healthcare access among TG women in this setting. The aim of this study was to explore individual, social-structural and environmental factors associated with healthcare avoidance among TG women in Argentina.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
89
1
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 31 publications
7
89
1
18
Order By: Relevance
“…A more detailed description of our sample and recruitment procedures has been described previously. 5,37,38 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more detailed description of our sample and recruitment procedures has been described previously. 5,37,38 …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, to be consistent with previous research examining PrEP acceptability among transgender women, 32,44–46 we included a variable addressing lifetime gender-based discrimination in healthcare settings (yes vs. no), assessed with the question: “Due to your transgender identity, have you ever experienced discrimination from physicians, nurses, or other healthcare workers?” as defined in previous studies with this population. 5,37,38 …”
Section: Methodsmentioning
confidence: 99%
“…Among TW in Peru, the high prevalence of cross-sex hormone use without physician prescription or medical supervision is well-documented [3842]. In a 2009 survey, 87% of TW participants reported having ever used hormone therapy, though only 20% reported being prescribed hormones by a physician, and 66% reported obtaining hormones by a friend or acquaintance [3].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research has focused on women sex workers with a growing body of research on trans sex workers –those whose gender identity or expression differs from their assigned birth sex—emerging in global settings (Bhattacharjya et al, 2015; Infante, Sosa-Rubi, & Cuadra, 2009; Rhodes, Simic, Baros, Platt, & Zikic, 2008; Socías, Marshall, Arístegui, Romero, et al, 2014). This research suggests that trans sex workers may be particularly vulnerable to violence due to a complex interplay of social-structural contexts.…”
mentioning
confidence: 99%
“…It has been suggested that sex work is one of a few viable economic opportunities for trans individuals (Poteat et al, 2015; Xavier et al, 2013) and a relationship has been found between barriers to economic security and violence among trans persons (Lombardi, et al, 2001). Trans sex workers are also known to experience high rates of police-perpetuated violence in some settings (Rhodes, et al, 2008), and the adverse impact of such violence on healthcare avoidance by trans sex workers has been observed (Socías, Marshall, Arístegui, Romero, et al, 2014). Therefore, social-structural contexts shape trans persons’ experiences of violence and associated impacts on health.…”
mentioning
confidence: 99%